Análise do comportamento fluvial a partir da classificação dos estilos fluviais do Rio Taperoá - semiárido paraibano - Maia, Rachel de Souza (2019)
In semiarid areas such as Northeastern Brazil, the water problem is more visible and complex due to the low volume of rainfall and its irregular distribution, spatially and temporally, being associated with the high evapotranspiration rates that make the water reserves scarce. Thus, public policies for the semi-arid are focused on the construction of dams as a form of water resources management, however, the planning of these reservoirs is usually based only on the amount of precipitation from the drainage area, which would be the total available water. to the reservoir. The main objective of the research is to analyze the fluvial behavior, focusing on the environmental and geomorphological condition of the rivers and their adjustment capacity. For this, the use and application of the theoretical-methodological proposal Fluvial Styles, which aims to characterize river channels. To achieve the research objectives, some methodological steps were necessary, such as: use of geoprocessing and remote sensing, which preceded the field work in July and August 2018 and April and May 2019, analysis and mapping of river styles and capacity. of adjustment. Thus, thematic maps of DEM, slope, geomorphological, landscape unit, geology, land use and soils were made, being necessary data to reach the research objectives and obtained from different sources: Paraíba Soil Survey, AESA ( Paraíba State Water Management Executive Agency) among others. Still, to have the development of elevation models (MDEs) and slope map, remote sensing was used from the Advanced Land Observing Satellite (ALOS) images with a resolution of 12.5 m from 2011. and for the land use map, false color classification (RGB, Red, Green and Blue) 7.5 (3) spectral bands were made from the LANDSAT 8 OLIE sensor images, being a better way of knowing the basin in question. In the Taperoá River Basin, the styles found were: drainage head, rectilinear channel, continuous plain sandy channel, discontinuous plain sandy channel, irregular discontinuous plain channel, multiple channels with rocky outcrop and sandy channel with threshold. In the Taperoá River Basin were found levels of adjustment capacity between high, moderate and low channel adjustment capacity. Thus, the assessment of the ability to adjust and river styles provides information that is fundamental, regarding the creation of future scenarios from possible coherent structural changes for the geomorphological processes in the river system. Thus, by recognizing the key points to identify the ability to adjust, such as mapping river styles and identifying contemporary adjustments in light of changes and likely changes in river courses, it became possible to apply the methodology, demonstrating satisfactory, bringing together the data necessary to.